Longitudinal Evolution of the Concentration of Gangliosides GM3 and GD3 in Human Milk. Issue 10 (4th September 2014) - Giuffrida, Francesca; Elmelegy, Isabelle Masserey; Thakkar, Sagar K.; Marmet, Cynthia; Destaillats, Frédéric
Abstract: It has been reported that dietary gangliosides may have an important role in preventing infections and in brain development during early infancy. However, data related to the evolution of their concentration over the different stages of lactation are scarce. Liquid chromatography coupled with electrospray ionization high resolution mass spectrometer (LC/ESI‐HR‐MS) has been optimized to quantify the two major ganglioside classes, i.e., aNeu5Ac(2‐8)aNeu5Ac(2‐3)bDGalp(1‐4)bDGlcp(1‐1)Cer (GD3) and aNeu5Ac(2‐3)bDGalp(1‐4)bDGlcp(1‐1)Cer (GM3) in human milk. Gangliosides were extracted using chloroform and methanol, further purified by solid‐phase extraction and separated by reversed‐phase liquid chromatography. Repeatability, intermediate reproducibility, and recovery values were assessed to validate the method. In human milk, GD3 and GM3 could be quantified at the level of 0.1 and 0.2 μg/mL, respectively, with relative standard deviation of repeatability [CV(r)] and intermediate reproducibility [CV(iR)] values ranging from 1.9 to 15.0 % and 1.9 to 22.5 %, respectively. The described method was used to quantify GD3 and GM3 in human milk samples collected from 450 volunteers between 0 and 11 days and at 30, 60 and 120 days postpartum, providing for the first time the concentration of these minor lipids in a large cohort. The content of total gangliosides ranged from 8.1 and 10.7 μg/mL and the mean intake of gangliosides in infants 30, 60 and 120 days postpartum could be estimated at about 5.5, 7.0 and 8.6 mg of total gangliosides per day, respectively, when infants were exclusively breastfed.